A biblioteca universitária como instrumento para a formação acadêmica : significados dos profissionais da Biblioteca Regional da UFMT/Câmpus Rondonópolis - Valeriano, Renata Bezerra (2018)
Higher education has undergone many transformations due the advances of the science and technology of the information and communication, at the same time the access to higher education has been expanded, providing academic education to many Brazilians. In this scenario of changes, the university libraries have also advanced, being necessary the constant update of the bibliographical archive, the supply of new information services and a team of prepared professionals to meet the needs of the information and research of the academic community. Therefore, the current study has the objective of investigating what meaning the administrative technician servants in Education of the Regional Library of UFMT/Campus of Rondonópolis assign to the existing relationship between the exercise of their function and the academic education, in the perspective of contributing to the redimensioning of their professional practice. In this aspect, the theoretical reference about the role of the university libraries and of its staff was constructed mainly based on Amante (2007; 2010), Amante, Extremeño Placer e Costa (2012), Destro (1996), Gelfand (1968), Gómez Hernández e Licea de Arenas (2005), Milanesi (1983; 2013), Orera Orera (2005), Ranganathan (2009), Sepúlveda (2002) and Thompson e Carr (1990), which also theoretically support the data analysis. To reach the research objectives, we embraced the Communicative Investigation Methodology, based on the theoretical-methodological premise of Habermas (2012) and Freire (1991; 2001; 2011; 2013; 2015a; 2015b), which besides describing and explaining reality, comprehending it and interpreting, also aims at transforming it, seeking to understand how the meanings construct themselves communicatively. Thus, we held groups of communicative discussion with four professionals of the referred Library. The data analysis was conducted intersubjectively between the researcher and the participants according to the four topics discussed in the groups. The interpretation of the data of each topic resulted on a synthesis of the excluding dimensions and transformations. The resulting information of the empirical research shows that the meaning construction of the professionals in relation to the exercise of their function in the university library and the academic education are directly related to the lack of in-service education and training, since the four participants are administrative technician servants in Education, with diverse preparations, yet no training from UFMT. Another identified aspect is the absence of meaning attributed by the actual academic community: management, faculty, students and administrative technician servants of UFMT.